Decentralization and reform of local self-government in Ukraine - Yurkevych, Iryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Theoretical aspects of decentralization as foundation of establishment of democratic model of governance are analyzed in the article. Importance of implementation of the reform of decentralization of power for development of Ukraine as democratic constitutional state is proved. The legislative framework for implementation of the reform of decentralization of power is analyzed. The author investigates the problems of decentralization in Ukraine, determines advantages of decentralized management and possible risks